Demystifying pulmonary vascular complications in severe coronavirus disease-19 pneumonia (COVID-19) in the light of clinico-radiologic-pathologic correlation. Issue 196 (December 2020) - Parry, Arshed Hussain; Wani, Abdul Haseeb; Yaseen, Mudasira; Dar, Mohd Iqbal
Highlights: Small pulmonary vessel changes are a unique imaging feature of COVID-19 pneumonia. Autopsy studies reveal a very high incidence of peripheral pulmonary thrombosis. Risk of thrombosis is high in severe COVID-19 despite anticoagulation. Mounting evidence suggests immunothrombosis as a contributory cause of thrombosis. Combined inflammation reduction and anticoagulation seems to be a rational therapeutic protocol.